DESIGN OF BORED PILE FOUNDATION LIFESTYLE CENTER SUMMARECON BANDUNG PROJECT - HAWARI (NIM: 15013154), KASYFU
Summarecon Bandung is a self-contained area located in East Bandung area consisting of residential, commercial, and Summarecon Technopolis harmonious places to live, work, and recreation. Along with the development, the area will cause a change of land use into a center of activity, one of which is a lifestyle center. Lifestyle center must be supported by foundation which has bearing capacity that can resist against lifestyle centerÃ‚Â’s structural load. The type of foundation used in this structure is bored pile foundation. The method used for calculating the axial capacity of single pile is the static method that formulated by Reese & Wright and Meyerhoff. Axial bearing capacity calculations of pile refer to ASD (Allowable Stress Design). Then lateral capacity of single pile was calculated using ENSOFT LPILE program. For the analysis of group piles to find out the actual displacement and forces that occurred on each single pile in a group were done by the program ENSOFT GROUP. Next, the settlement of group pile that was calculated. Settlement was occured consists of two type, there are elastic settlement and consolidation settlement. Settlement of group pile calculated by Raft Equivalent method, and the differential settlement between each column will be checked.